Evolutionary Physiology and Biochemistry Advances and Perspectives (IntechOpen, 2018)
In 2016, it was 60 years since the eminent Soviet researcher, a disciple and a successor of Ivan Pavlov, Leon Orbeli had proclaimed the birth of a new branch of physiology, evolutionary physiology. In the same year, his ideas were embodied in the foundation in Leningrad, now Saint Petersburg, of the present Sechenov Institute of Evolutionary Physiology and Biochemistry of the Russian Academy of Sciences. This anniversary book includes the selected works carried out recently by his followers at the same institute. While addressing some hot aspects of evolutionary physiology and biochemistry, they demonstrate that this branch of physiology really represents a discipline in its own right.